Improvement of CO2/N2 separation performance by polymer matrix cellulose acetate butyrate - Lee, R.; Jawad, Z.; Ahmad, A.; Ngo, J.; Chua, Han Bing (2017)
© Published under licence by IOP Publishing Ltd. With the rapid development of modern civilization, carbon dioxide (CO 2 ) is produced in large quantities and mainly generated from industrial sectors. The gas emission is the major contributor to global warming. To address this issue, the membrane technology is implemented for the CO 2 removal, due to the energy efficiency and economic advantages presented. Cellulose acetate butyrate (CAB) is selected as the polymeric material, due to the excellent film-forming properties and capable of developing a defect-free layer of neat membrane. This study described the fabrication development of CAB using a wet phase inversion method with different casting conditions. Where the composition of the casting solutions (3-5 wt %) and solvent evaporation time (4-6 min) were determined. The outcomes of these dominant parameters were then used to determine the best CAB membrane for CO 2 /Nitrogen (N 2 ) separation and supported by the characterization i.e. scanning electron micrograph. Gas permeation measurements showed satisfactory performance for CAB membrane fabricated with 5 min evaporation time and 4 wt% polymer composition (M2). Where, its permeance and selectivity are 120.19 GPU and 3.17, respectively. In summary, this study showed a brief outlined of the future direction and perspective of CAB membrane for CO 2 /N 2 separation.